EXPLORING STUDENTS' EXPERIENCES IN UTILIZING THE OPAC IN THE MEDAN TOURISM POLYTECHNIC LIBRARY THROUGH THE THINK-A LOUD PROTOCOL - Siregar, Tiopan Daris; Sayekti, Retno (Pena Cendekia Insani, 2025)
This study aims to explore students' experiences in using the Online Public Access Catalog (OPAC) at the Medan Tourism Polytechnic Library using the Think-Aloud Protocol (TAP) method. A total of 15 students who had used the OPAC at least twice were purposively selected as respondents. Data were collected through observations of collection search tasks and semi-structured interviews, then analyzed using Reflexive Thematic Analysis (RTA) associated with ISO 9241-11 indicators and the Technology Acceptance Model (TAM) framework. The results showed that 70% of students experienced difficulty using the advanced search feature, took an average of five minutes to find a book title, and 60% considered the OPAC interface less intuitive. The main obstacles included an interface that was less user-friendly, low digital literacy, and minimal socialization from librarians. These findings expand the theoretical understanding of the relationship between digital literacy and perceived ease of use in the context of vocational education, while also emphasizing the importance of a user-centered design (UCD) approach in OPAC development. This study recommends simplifying the interface, integrating OPAC training into student orientation programs, and strengthening the role of librarians in digital literacy support, so that OPAC can be optimally utilized to support academic activities.